Negative active material, secondary battery, and electric device
Patent Information
- Application Number
- CN202611359348.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-20
AI Technical Summary
然而,由于石墨化辅料自身特殊的结构和较软的质地,该类材料难以粉碎,成品中易残留大颗粒;该大颗粒在复合涂布时容易产生刮带缺陷,同时还存在压实密度偏低、比表面积偏大等问题
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application belongs to the field of secondary batteries, and specifically relates to negative electrode active materials, secondary batteries and electrical equipment. Background Technology
[0002] With the rapid development of the new energy industry, the demand for cost reduction in power batteries is becoming increasingly prominent. Lithium-ion rechargeable batteries, as the most widely used type of rechargeable battery, rely heavily on their negative electrode active materials for energy density, cycle life, and rate performance. Artificial graphite, due to its excellent cycle stability and good layered structure, has been widely used as the negative electrode active material for lithium-ion batteries.
[0003] In recent years, producing artificial graphite using graphitized auxiliaries as raw materials has become an effective way to reduce the manufacturing cost of core processes. However, due to the special structure and soft texture of graphitized auxiliaries, these materials are difficult to pulverize, and large particles are easily left in the finished product. These large particles are prone to causing scratching defects during composite coating, and there are also problems such as low compaction density and large specific surface area. These shortcomings not only limit the application scenarios of this type of low-cost anode active material, but also affect the kinetic performance and cycle stability of secondary batteries. Therefore, how to reduce costs while taking into account the particle size, specific surface area, compaction density, and coating processability of the anode active material is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] In a first aspect of this application, a negative electrode active material is provided. The negative electrode active material includes a graphite core and an amorphous carbon layer disposed on at least a portion of the surface of the graphite core. The specific surface area Rm of the negative electrode active material is... 2 / g is 1m 2 / g~6 m 2 / g; the sphericity ψ of the negative electrode active material is 0.7~0.96; the X-ray diffraction (XRD) pattern of the negative electrode active material has a first diffraction peak in the range of diffraction angle 2θ of 26.5°~26.8°, and the peak intensity of the first diffraction peak is V1; it has a second diffraction peak in the range of diffraction angle 2θ of 41.7°~42.5°, and the peak intensity of the second diffraction peak is V2, and the half width at half maximum of the second diffraction peak is W2°, and satisfies: 0.136≤V2 / [(W2-0.7)×V1]≤1.05.
[0005] The negative electrode active material provided in this application is a core-shell structure consisting of a graphite core and an amorphous carbon layer. The graphite core provides the main lithium storage capacity, with lithium ions intercalating and deintercalating within the interlayer structure of the graphite to achieve a reversible electrochemical reaction. The amorphous carbon layer at least partially coats the surface of the graphite core. On the one hand, it can fill the pores and defects on the surface of the graphite core, reducing the area of direct contact between the negative electrode active material and the electrolyte, and reducing the initial irreversible capacity loss. On the other hand, the isotropic nature of the amorphous carbon layer provides more lithium ion intercalation sites, which is beneficial for improving the rate performance of the negative electrode active material.
[0006] By controlling the specific surface area R of the negative electrode active material to 1m 2 / g~6m 2 A specific surface area of / g can achieve a balance between electrolyte wettability and side reaction suppression. Within the above-mentioned range, the contact area between the negative electrode active material and the electrolyte is appropriate, preventing excessive consumption of lithium ions and electrolyte to form a solid electrolyte interface film during the formation stage. This is beneficial for improving initial efficiency and reducing gas production. Simultaneously, it ensures sufficient wetting of the negative electrode active material by the electrolyte, ensuring smooth lithium ion transport pathways and improving the rate performance of the secondary battery.
[0007] Controlling the sphericity ψ of the negative electrode active material within the range of 0.7 to 0.96 is beneficial for increasing the compaction density of the negative electrode active material, thereby improving the energy density of the secondary battery. Within this range, the sphericity reduces the porosity between particles, resulting in a corresponding increase in powder compaction density. Simultaneously, it helps maintain uniform flow of the negative electrode slurry during coating, reducing coating defects caused by irregular particle shapes.
[0008] The XRD pattern of the negative electrode active material shows diffraction peaks at 26.5°~26.8° corresponding to the (002) crystal plane diffraction peaks of graphite. The peak intensity V1 reflects the degree of graphitization and can be used as a benchmark for evaluating the crystallinity of the material. The diffraction peaks at 41.7°~42.5° correspond to the (100) crystal plane diffraction peaks of graphite. The peak intensity V2 and half-maximum width W2 further reflect the degree of crystallinity perfection and crystallite size of the material. With increasing graphitization, the (100) peak intensity V2 increases and the half-maximum width W2 narrows; with increasing disordered structural features in the material, V2 decreases and W2 increases. Therefore, the combined changes in V2 and W2 can characterize the relative state of ordered and disordered structures in the material.
[0009] By controlling the value of V2 / [(W2-0.7)×V1] within the range of 0.136 to 1.05, the degree of graphitization of the negative electrode active material can be kept at a moderate level. This parameter comprehensively reflects the perfection of the material's crystal structure. Controlling this parameter within the above range is beneficial for achieving a reasonable match between the ordered graphite structure and the disordered carbon structure in the material: the ordered graphite structure can provide higher specific capacity and compaction density, while the disordered carbon structure can improve the isotropy of the material and form smooth lithium-ion diffusion channels, thereby improving kinetic performance and fast-charging performance. Therefore, by controlling this parameter within the above range, a balance can be achieved between specific capacity, compaction density, and kinetic performance.
[0010] The aforementioned amorphous carbon layer, specific surface area R, sphericity ψ, and XRD composite parameters are interrelated. Specifically, the amorphous carbon layer and specific surface area primarily affect the interfacial reactions of the negative electrode active material and the formation of the solid electrolyte interfacial film; sphericity and compaction density mainly affect powder processing, electrode compaction, and volumetric energy density; and the XRD composite parameters primarily reflect the relative state of the ordered and disordered structures of graphite microcrystals. By ensuring that these parameters are simultaneously within specified ranges, the ion transport limitation that may be caused by individually increasing compaction density or crystal order can be reduced, as well as the increase in side reactions that may be caused by individually increasing specific surface area or disordered structure. This is beneficial for balancing initial coulombic efficiency, volumetric energy density, rate performance, cycle stability, and processing consistency.
[0011] In some embodiments, the negative electrode active material satisfies: 0.6≤(ψ-0.6)×R≤0.9.
[0012] In some embodiments, the value of (ψ-0.6)×R can be a range of one or any two of 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, and 0.9.
[0013] The parameter (ψ-0.6)×R couples the sphericity ψ with the specific surface area R. The purpose of subtracting the empirical coefficient 0.6 from the sphericity ψ is to increase the sensitivity of characterizing the differences in sphericity between different materials. For example, when sphericities are similar (e.g., 0.80 and 0.85), directly comparing the differences in sphericity is only about 6%, while subtracting 0.6 amplifies the difference to 25%, making the parameter more sensitive to changes in sphericity. Simultaneously, since this type of negative electrode active material prepared using graphitized excipients has a larger specific surface area than conventional artificial graphite, multiplying (ψ-0.6) by R can further amplify the characteristic differences between materials, which is beneficial for more accurate characterization and screening of negative electrode active materials with target microstructures. Therefore, by controlling (ψ-0.6)×R within the range of 0.6 to 0.9, the matching relationship between sphericity and specific surface area can be constrained simultaneously, ensuring a balance between the coating processability and electrochemical performance of the negative electrode active material.
[0014] In some embodiments, the negative electrode active material satisfies: 2%≤(m1-m2)≤14%, where m1 represents the normalized remaining mass fraction of the thermogravimetric curve of the negative electrode active material at 410℃, and m2 represents the normalized remaining mass fraction of the thermogravimetric curve of the negative electrode active material at 495℃.
[0015] In some embodiments, the value of (m1-m2) can be a range of one or any two of 2%, 4%, 6%, 8%, 10%, 12% and 14%.
[0016] Thermogravimetric analysis (TGA) is an effective method for characterizing the structural features of carbonaceous materials. Normalized residual mass fraction (NRS) refers to the percentage of remaining mass at a specific temperature after the sample mass is normalized to its initial mass in a TGA test. During the heating process of negative electrode active materials, different carbon components undergo oxidation and weight loss in different temperature ranges. The difference (m1-m2) between the normalized residual mass fraction m1 at 410℃ and the normalized residual mass fraction m2 at 495℃ reflects the relative content and thermal stability differences between amorphous carbon components and graphite crystal components in the negative electrode active material. This type of negative electrode active material prepared using graphitized additives has a porous structure; its amorphous carbon layers and some disordered carbon components begin to oxidize and lose weight at lower temperatures, while the more graphitized core only undergoes oxidation and weight loss at higher temperatures. Therefore, by controlling (m1-m2) within the range of 2% to 14%, the ratio between the amorphous carbon layer and the graphite core, as well as the uniformity of the amorphous carbon layer coating, can be indirectly regulated, thereby affecting the first-time efficiency, cycle performance, and interfacial compatibility with the electrolyte of the negative electrode active material.
[0017] In some embodiments, m1 is 97.2%~99.6% and m2 is 89.9%~96.5%.
[0018] By controlling m1 within the range of 97.2% to 99.6%, the anode active material can maintain suitable thermal stability at lower temperatures, avoiding premature and excessive oxidation weight loss due to excessive amorphous carbon layers or defective carbon content, thereby reducing the number of active sites on the material surface and their side reactions with the electrolyte. Simultaneously, controlling m2 within the range of 89.9% to 96.5% ensures suitable mass loss of the anode active material within the temperature range of 410℃ to 495℃, indicating a reasonable proportional relationship between the amorphous carbon layer, disordered carbon components, and graphite crystal components. This is beneficial for improving the uniformity of the amorphous carbon layer coating and the structural stability of the graphite core, thus balancing the initial coulombic efficiency, rate performance, cycle performance, and interfacial stability of the anode active material.
[0019] In some embodiments, the compaction density P g / cm³ of the negative electrode active material at 5T 3 1.55 g / cm 3 ~1.67 g / cm 3 .
[0020] Controlling the compaction density P of the negative electrode active material at 5T to 1.55 g / cm³~1.67 g / cm³ enables the formation of suitable contact states and pore structures between particles, which is conducive to the full wetting of the electrolyte and the construction of smooth lithium-ion transport channels, thereby improving the kinetic performance and rate performance of the negative electrode active material. At the same time, it is beneficial to increase the content of active material per unit volume, so that the negative electrode sheet has both high energy density and good kinetic performance.
[0021] In some embodiments, the volumetric cumulative particle size Dv of the negative electrode active material 50 The size ranges from 6μm to 12μm.
[0022] In some embodiments, Dv 50 It can be a range of one or any two of 6μm, 7μm, 8μm, 9μm, 10μm, 11μm and 12μm.
[0023] Dv 50 This represents the median particle size of the negative electrode active material, i.e., the particle size corresponding to a 50% volumetric cumulative distribution. (Dv) 50 By controlling the particle size within the range of 6μm to 12μm, both the processability and coating properties of the negative electrode active material can be balanced. (The last part, "Dv," appears to be an unrelated fragment and is omitted from the translation.) 50 Controlling the particle size within the range of 6μm to 12μm allows for suitable solid-phase diffusion paths within the particles, which facilitates rapid lithium-ion transport and improves concentration polarization, thereby enhancing high-rate charge-discharge performance. Simultaneously, it enables the negative electrode active material to possess a suitable specific surface area and good particle dispersibility, which is beneficial for forming a stable electrolyte interface and improving the dispersion uniformity and coating quality of the slurry.
[0024] In some embodiments, the volumetric cumulative particle size Dv of the negative electrode active material 99 The range is 30μm to 42μm.
[0025] In some embodiments, Dv 99 It can be a range of 30μm, 33μm, 36μm, 39μm and 42μm or any two of them.
[0026] Dv 99 This represents the particle size at which the volumetric cumulative distribution reaches 99%, which characterizes the size level of the largest particles in the negative electrode active material. (Dv) 99Controlling the particle size to 30μm~42μm can effectively avoid scratching defects caused by large particles during the composite coating process. The above Dv 99 The range is suitable for the relatively soft texture of this type of material, and the target particle size can be obtained by using appropriate crushing force, which is conducive to maintaining the integrity of particle structure, suitable specific surface area and good processing economy.
[0027] In some embodiments, the Dv of the negative electrode active material 50 and Dv 99 Satisfies: 1.7 ≤ (Dv) 99 -Dv 50 ) / Dv 50 ≤2.8.
[0028] In some embodiments, (Dv) 99 -Dv 50 ) / Dv 50 The value can be a range of one or both of the following: 1.7, 1.9, 2.1, 2.3, 2.5, and 2.8.
[0029] (Dv 99 -Dv 50 ) / Dv 50 This primarily characterizes the degree of extension of the tail portion of coarse particles relative to the median particle size. Controlling this ratio between 1.7 and 2.8 achieves a reasonable particle size distribution. A wider particle size distribution facilitates the filling of gaps between larger particles by smaller particles, increasing the compaction density of the powder and electrode. Simultaneously, maintaining an appropriate ratio and size difference between coarse and fine particles promotes uniform dispersion of the slurry and improves coating consistency. Therefore, the aforementioned particle size distribution can enhance the bulk density of the particles, enabling the negative electrode to possess both high energy density and good processing performance.
[0030] In some embodiments, the degree of graphitization of the negative electrode active material is 91% to 96%.
[0031] In some embodiments, the degree of graphitization may be a range of one or any two of 91%, 92%, 93%, 94%, 95%, and 96%.
[0032] The degree of graphitization reflects the perfection of the graphite crystal structure in carbonaceous materials. Controlling the degree of graphitization between 91% and 96% allows for a balance between specific capacity and kinetic performance in the anode active material. Higher graphitization results in a material closer to the layered structure of ideal graphite, leading to a higher theoretical specific capacity. However, it also enhances anisotropy, increases resistance to interlayer lithium-ion diffusion, and limits rate performance. Anode active materials prepared using graphitized additives have a lower degree of graphitization compared to conventional artificial graphite due to the structural characteristics of the raw materials themselves. This is consistent with the broader peak shape and lower peak intensity in their XRD patterns. A moderate degree of graphitization endows the material with better isotropy and a porous structure, which facilitates lithium-ion insertion and extraction from multiple directions, improving fast-charging capability.
[0033] In a second aspect of this application, a secondary battery is provided. The secondary battery includes a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes the negative electrode active material described in any of the embodiments of the first aspect above. On the surface of the negative electrode active material layer, the number of continuous scratches greater than or equal to 3 mm is less than or equal to one. In this embodiment, the fact that the number of continuous scratches greater than or equal to 3 mm on the surface of the negative electrode active material layer is less than or equal to one indicates that scratch defects occurring during the coating process of the negative electrode slurry are effectively suppressed. Reducing the number of continuous scratches can avoid uneven distribution of electrons and ions, which is beneficial for suppressing lithium plating on the negative electrode sheet.
[0034] In some embodiments, the curvature κ of the formation differential capacity curve of the secondary battery at 2480mV satisfies: 0.09≤κ≤0.15.
[0035] In some embodiments, κ can be a range of one or any two of 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, and 0.15.
[0036] The formation differential capacity curve (dQ / dV curve) is obtained by differentiating the capacity-voltage curve. The peak shape on the curve reflects the lithium intercalation reaction stage and structural characteristics of the anode active material. The curvature κ at 2480 mV characterizes the sharpness of the differential capacity curve peak at this position. For conventional artificial graphite with high crystallinity, the lithium intercalation reaction stage is clear, the peak shape is sharp, and the corresponding curvature is large. However, for this type of anode active material prepared with graphitized excipients, due to its porous structure and relatively low degree of graphitization, the peak shape is wider and smoother, and the curvature at 2480 mV is correspondingly smaller. By controlling the curvature κ within the range of 0.09 to 0.15, anode active materials with suitable microstructures can be screened. These materials maintain sufficient graphitization to provide high specific capacity while possessing porous and moderately disordered structural characteristics to improve kinetic performance.
[0037] In some embodiments, the secondary battery further includes a positive electrode sheet. The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The positive active material layer includes a positive active material.
[0038] In some embodiments, the positive electrode active material may include at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based materials.
[0039] In some embodiments, the secondary battery further includes a separator. The type of separator can be selected according to actual needs. Exemplarily, the separator can be a polypropylene membrane, a polyethylene membrane, a polyvinylidene fluoride membrane, an aramid membrane, or a coated and modified multilayer composite membrane.
[0040] In some embodiments, the secondary battery further includes an electrolyte, which may be an organic or inorganic solution with lithium salt as the solute.
[0041] In some embodiments, the secondary battery also includes an outer packaging, which can be rigid packaging, such as a hard plastic shell, aluminum shell, steel shell, etc. The outer packaging of the secondary battery can also be flexible packaging, such as a pouch-type soft pack, and the material of the soft pack can be polypropylene, polybutylene terephthalate, and / or polybutylene succinate.
[0042] In a third aspect of this application, an electrical device is provided. The electrical device includes the secondary battery described in the second aspect, which serves as the power supply for the electrical device.
[0043] In some embodiments, the electrical equipment can be application devices such as vehicles, mobile phones, portable devices, laptops, ships, spacecraft, electric toys, and power tools. Vehicles can be new energy vehicles, including pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles; spacecraft include airplanes, rockets, space shuttles, and spacecraft; electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys; power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers. This application does not impose special limitations on the above-mentioned devices.
[0044] It should be understood that the content described in this section is not intended to limit the key or essential features of the embodiments of this application, nor is it intended to restrict the scope of this application. Other features of this application will become readily apparent from the following description. Detailed Implementation
[0045] Embodiments of this disclosure will now be described in more detail. It should be understood that this disclosure may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of this disclosure to those skilled in the art.
[0046] The term "comprising" and its variations as used herein signify open inclusion, i.e., "including but not limited to". Unless otherwise stated, the term "or" means "and / or". The term "based on" means "at least partially based on". The terms "one example embodiment" and "one embodiment" mean "at least one example embodiment". The term "another embodiment" means "at least one additional embodiment". The terms "first", "second", etc., may refer to different or the same objects.
[0047] Currently, the demand for cost reduction in power batteries is becoming increasingly prominent. Using graphitized auxiliary materials to produce artificial graphite can effectively reduce the manufacturing costs of core processes. However, due to the unique structure and relatively soft texture of graphitized auxiliary materials, it is difficult to completely crush large particles during the pulverization process, resulting in large particles in the finished negative electrode active material. When this type of negative electrode active material is applied to the composite coating process, large particles easily form scraping defects at the coating blade, seriously affecting the electrode quality and production yield. Simultaneously, this type of material also suffers from low compaction density and high specific surface area. The former limits the energy density of secondary batteries, while the latter leads to increased initial irreversible capacity loss and electrolyte consumption.
[0048] Furthermore, due to the structural characteristics of graphitized additives, anode active materials prepared from them typically possess a porous structure, with a lower degree of graphitization compared to conventional artificial graphite. While this structural feature is beneficial to the rapid transport of lithium ions and rate performance to some extent, it also introduces microstructural characteristics distinct from conventional artificial graphite, such as insufficient crystallinity, broad and gentle XRD diffraction peaks, and flat differential capacity curve peaks. The core technical problem this disclosure aims to solve is how to maintain a low-cost advantage while optimizing particle size distribution, spheroidization, and coating processes to achieve both uniform small particle size and high compaction density in the anode active material, reduce the risk of scratching during composite coating, and possess good kinetic performance.
[0049] This disclosure provides a negative electrode active material comprising a graphite core and an amorphous carbon layer at least partially disposed on the surface of the graphite core. By synergistically optimizing and controlling the specific surface area, sphericity, compaction density, and XRD pattern parameters of the negative electrode active material, this material achieves a balance between uniform small particle size, high compaction density, and suitable specific surface area while maintaining low cost. This negative electrode active material reduces scratch defects in composite coating processes and exhibits excellent kinetic performance, thereby improving the rate performance and cycle stability of secondary batteries.
[0050] Example 1 (1) Preparation of positive electrode sheet The positive electrode current collector is a double-sided carbon-coated aluminum foil with a thickness of 8μm and a carbon layer thickness of 1μm on each side.
[0051] The positive electrode active materials LiFePO4, carbon black, polyvinylidene fluoride (PVDF), and carbon nanotubes (CNTs) were mixed in a mass ratio of 95:2.7:1.8:0.5. N-methylpyrrolidone (NMP) solvent was added, and the mixture was stirred under vacuum to obtain a positive electrode slurry. The solid content of the positive electrode slurry was 68%. The positive electrode slurry was uniformly coated onto both sides of the positive electrode current collector aluminum foil, air-dried at room temperature, and then transferred to an oven for further drying. Finally, the foil was rolled and cut to obtain the positive electrode sheet.
[0052] (2) Preparation of negative electrode active material Graphitization auxiliary material crushing: The resistance material treated by the Acheson furnace is crushed using a crusher, with the main power adjusted to 400kW and the air intake volume to 75 m³ / h. 3 / min, feed rate 800 kg / h, crushing time 50 min.
[0053] Spheroidizing and shaping: The crushed material is placed in a spheroidizing and shaping machine with a feeding frequency of 30Hz, a grinding disc spacing of 80μm, a shaping speed of 900rpm, a shaping time of 25min, and a grading frequency of 55Hz.
[0054] Liquid-phase coating and calcination: Based on the mass of the shaped material, 8 wt% liquid-phase asphalt is added to the shaped material. The mixture is then homogenized in a liquid-phase coating machine to obtain a coating precursor. The coating precursor is then transferred to a mechanical fusion machine for mechanical fusion at a speed of 800 rpm for 15 minutes.
[0055] The mechanically fused precursor was placed in a nitrogen atmosphere furnace and heated to 800°C at a rate of 2°C / min, then to 1250°C at a rate of 5°C / min, held for 4 hours, and then cooled to below 100°C under nitrogen protection to obtain the calcined material.
[0056] Dispersion and sieving: After the calcined material is cooled down, it is dispersed at 30 rpm for 45 min using a VC mixer, and then sieved using a 300-mesh screen. The material under sieve is demagnetized to obtain the negative electrode active material.
[0057] (3) Preparation of negative electrode sheet: The negative electrode current collector is a copper foil with a thickness of 4.5 μm.
[0058] The negative electrode active material, conductive agent carbon black, binder styrene-butadiene rubber, and dispersant sodium carboxymethyl cellulose were mixed in a mass ratio of 96.5:0.5:1.5:1.5. Deionized water was added as a solvent, and the mixture was stirred under vacuum to obtain a negative electrode slurry. The solid content of the negative electrode slurry was 49%. The negative electrode slurry was uniformly coated on both sides of the negative electrode current collector copper foil, dried with hot air at 80°C, and then transferred to an oven for further drying. After rolling and cutting, the negative electrode sheet was obtained. The compacted density of the negative electrode sheet was 1.58 g / cm³. 3 .
[0059] (4) Secondary battery assembly Lithium hexafluorophosphate was dissolved in an organic solvent (composed of ethylene carbonate EC, dimethyl carbonate DMC, and ethyl methyl carbonate in a volume ratio of 1:1:1) to obtain an electrolyte with a LiPF6 concentration of 1 mol / L.
[0060] The negative electrode sheet is die-cut into a size of 45 mm × 58 mm using a die-cutting machine, and the positive electrode sheet is die-cut into a size of 43 mm × 56 mm using a die-cutting machine.
[0061] Polypropylene is used as the separator. The positive electrode, separator, and negative electrode are stacked in sequence, with the separator in the middle of the positive and negative electrodes. Then, they are wound into a bare cell and packed into a soft-pack casing. After top-side sealing, electrolyte injection, formation, sorting and other processes, a secondary battery is obtained.
[0062] The following methods were used to characterize the properties of the prepared negative electrode active material.
[0063] 1) Specific surface area R The specific surface area of the negative electrode active material was determined using the nitrogen adsorption method. The negative electrode active material samples were degassed under vacuum at 200℃ for 2 hours, and then nitrogen was used as the adsorbate gas to test the nitrogen adsorption isotherm. The specific surface area R of the negative electrode active material was calculated using the BET method, with units of m² / g. Each sample was tested in triplicate, and the arithmetic mean was taken.
[0064] 2) Sphericity ψ The sphericity of the negative electrode active material was tested using a dynamic particle image analyzer. The negative electrode active material was dispersed in anhydrous ethanol and ultrasonically dispersed for 2 min before dynamic image acquisition. Adhesive particles and incomplete particles intersecting the image boundaries were excluded, and at least 2000 valid particles were counted for each sample.
[0065] Based on the two-dimensional projected area A and the two-dimensional projected profile perimeter L of each particle, the sphericity of a single particle is calculated according to the following formula: ψ i =4πA / L 2 The sphericity ψ of the negative electrode active material is the arithmetic mean of the sphericity of all effective particles.
[0066] 3) Compacted density P under a 5T load A powder compaction density tester was used to add the negative electrode active material into a mold. A pressure of 5T was applied to the mold and held for 30 seconds. The height h of the powder block under the pressure was recorded.
[0067] The compaction density P is calculated using the following formula:
[0068] In the formula, m is the sample mass, d is the inner diameter of the mold, h is the height of the powder block under a 5 T load, and d and h are converted to cm in the calculation. The unit of P is g / cm³.
[0069] 4) The peak intensity V1 and half-width W1 of the first diffraction peak in the diffraction angle 2θ range of 26.5°~26.8° of the negative electrode active material, and the peak intensity V2 and half-width W2 of the second diffraction peak in the diffraction angle 2θ range of 41.7°~42.5°.
[0070] X-ray diffractometer was used with a Cu target; characteristic ray: Cu Kα; wavelength: λ = 0.15406 nm; scanning range: 10°~80° (2θ) to test the X-ray diffraction pattern of the negative electrode active material. The first diffraction peak was determined in the range of 2θ = 26.5°~26.8°, and the peak height after deducting the local background was denoted as V1, and its half-maximum width at half-maximum was denoted as W1. The second diffraction peak was determined in the range of 2θ = 41.7°~42.5°, and the peak height after deducting the local background was denoted as V2, and its half-maximum width at half-maximum was denoted as W2. Both W1 and W2 are expressed in 2θ angles, in degrees.
[0071] 5) The normalized residual mass fraction m1 at 410℃ and the normalized residual mass fraction m2 at 495℃ in the thermogravimetric curve of the negative electrode active material.
[0072] Thermogravimetric analysis (TGA) was used to test the thermogravimetric curves of the negative electrode active material. The negative electrode active material was placed in an alumina crucible and heated to 120℃ in air atmosphere for 10 min to remove adsorbed water. The sample mass after the holding period was recorded as the initial mass M0. Subsequently, the temperature was increased to 800℃ at a rate of 5℃ / min, and the remaining mass M at 410℃ and 495℃ were recorded. 410 and M 495 m1 = M 410 / M0, m2= M 495 / M0.
[0073] 6) Volumetric cumulative particle size Dv of the negative electrode active material 50 and Dv 99 A laser particle size analyzer was used to test the particle size distribution of the negative electrode active material.
[0074] Dv 50 This represents the particle size at which the cumulative volume fraction reaches 50% in the cumulative particle size distribution on a volume basis; Dv 99 This indicates the particle size at which the cumulative volume fraction reaches 99%. Each sample was tested in triplicate, and the arithmetic mean was taken.
[0075] 7) Degree of graphitization of the negative electrode active material The degree of graphitization was tested according to GB / T 24533-2019 "Graphite Anode Materials for Lithium-ion Batteries".
[0076] 8) The curvature κ of the formation differential capacity curve of the secondary battery at 2480 mV The battery was initially charged at a constant current rate of 0.33C in an environment of 25°C. Voltage and cumulative charging capacity data were collected at 1-second intervals, and the differential capacity curve (dQ / dV) was calculated. The curve was fitted and differentiated to calculate the curvature κ at a voltage of 2480 mV.
[0077] Examples 2-4 The difference from Example 1 is that by adjusting the amount of asphalt added and the process parameters of spheroidizing and shaping, the resulting negative electrode active material was tested and found to have different specific surface area R, sphericity ψ, and compaction density P at 5T.
[0078] Examples 5-6 The difference from Example 1 is that the compaction density P of the prepared negative electrode active material at 5T is different by adjusting the rotation speed of mechanical fusion.
[0079] Examples 7-10 The difference from Example 1 is that the graphitization additives used are different.
[0080] Examples 11-14 The difference from Example 1 is that the calcination temperature of the coated precursor is different, which results in different normalized residual mass fractions m1 at 410°C and m2 at 495°C in the thermogravimetric curve of the prepared negative electrode active material, as well as different curvatures κ of the differential capacity curve of the secondary battery at 2480 mV.
[0081] Examples 15-19 The difference from Example 1 lies in the different grading frequencies during the chemical shaping process, resulting in a different cumulative particle size Dv of the prepared negative electrode active material. 99 and Dv 50 different.
[0082] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that, by adjusting the amount of asphalt added and the process parameters for spheroidizing and shaping, the resulting negative electrode active material has a measured specific surface area R of 6.9 m². 2 The sphericity ψ is 0.61, and the compacted density P at 5T is 1.48 g / cm³. 3 .
[0083] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the calcination temperature was adjusted to retain the porosity of the negative electrode active material, thereby achieving a specific surface area R of 6.2 m². 2 / g.
[0084] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the crushing and shaping process parameters were adjusted so that the sphericity ψ of the negative electrode active material was 0.62.
[0085] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the crushing and shaping process parameters were adjusted so that the sphericity ψ of the negative electrode active material was 0.97.
[0086] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the graphitization auxiliary materials used are different (multiple graphitization materials with similar degrees of graphitization and different crystal orientations are mixed together), so that the peak intensity V1 of the first diffraction peak, the peak intensity V2 of the second diffraction peak, and the half width at half maximum (W2) of the second diffraction peak of the negative electrode active material satisfy V2 / [(W2-0.7)×V1]=1.930528.
[0087] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the graphitization auxiliary materials used are different (multiple graphitization materials with similar graphitization degree and different crystal orientations are mixed together), so that the peak intensity V1 of the first diffraction peak, the peak intensity V2 of the second diffraction peak, and the half width at half maximum (W2) of the second diffraction peak of the negative electrode active material satisfy V2 / [(W2-0.7)×V1]=0.052169.
[0088] The specific parameter settings for Examples 1-19 and Comparative Examples 1-6 are shown in Table 1.
[0089] Table 1
[0090] In Table 1, "R" refers to the specific surface area of the negative electrode active material, in m². 2 / g; “ψ” refers to the sphericity of the negative electrode active material; "P" refers to the compaction density of the negative electrode active material at 5T, expressed in g / cm³. 3 ; “V1” refers to the peak intensity of the first diffraction peak in the X-ray diffraction pattern of the negative electrode active material within the range of 26.5° to 26.8° diffraction angle 2θ. “V2” refers to the peak intensity of the second diffraction peak in the X-ray diffraction pattern of the negative electrode active material within the range of 41.7° to 42.5° diffraction angle 2θ. “W2” refers to the half-width at half-maximum (WHM) of the second diffraction peak in the X-ray diffraction pattern of the negative electrode active material within the diffraction angle 2θ range of 41.7° to 42.5°, in degrees. “m1” refers to the normalized residual mass fraction at 410℃ in the thermogravimetric curve of the negative electrode active material; “m2” refers to the normalized residual mass fraction at 495℃ in the thermogravimetric curve of the negative electrode active material; “Dv 50 "This indicates the particle size at which the cumulative volume fraction reaches 50% in the cumulative particle size distribution based on volume; “Dv 99 "" indicates the particle size at which the cumulative volume fraction reaches 99% in the cumulative particle size distribution based on volume; “κ” refers to the curvature of the formation differential capacity curve of the secondary battery at 2480 mV.
[0091] Performance testing: 1) Ratio performance At room temperature (25±2℃), the battery with SOC=0% state of charge was charged to 3.65V at a charging rate of 0.33C, and the capacity was recorded as C1; then at room temperature, the battery with SOC=0% state of charge was charged to 3.65V at a charging rate of 2C, and the capacity was recorded as C2; the capacity retention rate (%) was calculated as C2 / C1×100%, which was used as the test index for fast charging performance.
[0092] 2) Cyclic performance At 25±2℃, the battery was charged and discharged at a rate of 1C / 1C within a range of 2.5~3.65V. The specific capacity of the battery in the first cycle and the specific capacity of the discharge after 1000 cycles were recorded. The capacity retention rate after 1000 cycles was calculated as: (Specific capacity of discharge after 1000 cycles / Specific capacity of discharge after the first cycle) × 100%.
[0093] 3) Coating scraping test In the composite coating process, observe whether there are scratch defects caused by large particles on the surface of the electrode. Continuous scratches ≥3mm along the coating direction are judged as scratches. Visually inspect 5000 meters of electrode and record the number of scratches.
[0094] The performance test data of Examples 1-19 and Comparative Examples 1-6 are shown in Table 2.
[0095] Table 2
[0096] Referring to Examples 1-19 and Comparative Examples 1-6, and in conjunction with Tables 1 and 2, it can be seen that the secondary battery prepared using the negative electrode active material of this application correlates the amorphous carbon layer, specific surface area R, sphericity ψ, compaction density P at 5T, and XRD composite parameters. By limiting the above parameters within their respective ranges, the limitation of ion transport that may be caused by increasing the compaction density or crystal order alone can be reduced, and the increase of side reactions that may be caused by increasing the specific surface area or disordered structure alone can be reduced. This is beneficial to taking into account the initial coulombic efficiency, volumetric energy density, rate performance, cycle stability, and processing consistency.
[0097] Referring to Examples 1-19, the secondary batteries prepared in this application have a 0.33C charging capacity of 3162 mAh to 3196 mAh, a 2C charging capacity retention rate of 88.2% to 94.9%, and a 1000-cycle capacity retention rate of 89.6% to 91.5%. Furthermore, most examples did not exhibit scraping defects in the coating scraping test. In contrast, Comparative Examples 1-6 showed a 2C charging capacity retention rate of only 82.1% to 92.4%, a 1000-cycle capacity retention rate of 76.7% to 88.5%, and exhibited 2 to 5 scraping defects. This indicates that this application, through synergistic control of the particle morphology, surface structure, and graphitization degree of the negative electrode active material, can balance the fast-charging performance, cycle performance, and coating processing performance of the secondary battery.
[0098] Referring to Examples 1-4 and Comparative Examples 1-4, it can be seen that the matching relationship between the specific surface area R and sphericity ψ of the negative electrode active material has a significant impact on the overall battery performance. When (ψ-0.6)×R is controlled within the range of 0.64-0.9, the 2C charging capacity retention rate of Examples 1-4 reaches 93.2%-93.8%, and the 1000-cycle capacity retention rate reaches 90.4%-91.3%, with no scratching defects observed. When the sphericity is too low or the specific surface area and sphericity are not properly matched, as in Comparative Examples 1 and 3, the 2C charging capacity retention rate drops to 89.3% and 87.6%, respectively, and the 1000-cycle capacity retention rate drops to 76.7% and 83.5%, respectively, with scratching defects appearing. When the sphericity is too high, as in Comparative Example 4, the 2C charging capacity retention rate decreases to 82.6%, indicating that a suitable matching relationship between specific surface area and sphericity is beneficial for simultaneously improving electrode coating uniformity and lithium-ion transport performance.
[0099] Referring to Examples 1, 5, and 6, it can be seen that the compaction density P of the negative electrode active material under a 5T load also affects the rate performance of the battery. When the compaction density increases from 1.45 g / cm³ to 1.58 g / cm³, the 2C charging capacity retention rate increases from 92.6% to 93.4%; when the compaction density is further increased to 1.75 g / cm³, the 2C charging capacity retention rate decreases to 88.2%. This indicates that excessively high compaction density may lead to a reduction in electrode porosity and electrolyte wetting channels, thereby increasing lithium-ion transport resistance. Therefore, a balance needs to be struck between electrode energy density and rate performance.
[0100] Referring to Examples 7-10 and Comparative Examples 5 and 6, it can be seen that the X-ray diffraction composite parameter (V2 / [(W2-0.7)×V1]) has a significant impact on the fast charging and cycle performance of the secondary battery. When this parameter is in the range of 0.256356~1.045448, the 2C charging capacity retention rate of Examples 7-10 is 92.8%~94.3%, and the 1000-cycle capacity retention rate is 89.8%~91.5%, with no scratching defects. When this parameter is too high or too low, as in Comparative Examples 5 and 6, the 2C charging capacity retention rate drops to 82.1% and 83.6%, respectively, and the 1000-cycle capacity retention rate drops to 83.7% and 86.2%, respectively, with more scratching defects appearing. This indicates that a moderate ratio of ordered to disordered crystal structure is beneficial for balancing capacity utilization and lithium-ion diffusion kinetics.
[0101] Referring to Examples 11-14, it can be seen that the calcination temperature of the coated precursor alters the thermogravimetric characteristics of the negative electrode active material and the curvature κ of the formation differential capacity curve at 2480 mV. When κ increases from 0.11 to 0.17, the 2C charging capacity retention rate increases from 93.3% to 94.9%, but the capacity retention rate after 1000 cycles decreases from 91.3% to 89.6%, indicating that an excessively large curvature corresponds to a sharper lithium intercalation reaction peak. Although this is beneficial for short-term rate performance, it may exacerbate polarization and structural stress during cycling. Considering both rate performance and cycle performance, the battery exhibits better overall performance when κ is controlled within the range of approximately 0.11 to 0.14.
[0102] As can be seen from Examples 15-19, the particle size parameter of the negative electrode active material mainly affects the rate performance and coating processing stability of the battery. In Dv 50 The range is from 9.2 μm to 11.7 μm, and the Dv value is... 99 Within the particle size range of 30 μm to 42 μm, the capacity retention rate after 1000 cycles in Examples 15 to 19 remained at 90.8% to 91.4%, indicating that appropriate particle size distribution is beneficial to maintaining electrode structural stability; however, when Dv 99 Reaching 42 μm and comparable to Dv 50When the particle size distribution is 10.6 μm, the coating scraping test showed one scraping defect, indicating that a wide particle size distribution or a high proportion of large particles may reduce the consistency of the slurry coating.
[0103] The secondary battery prepared in this application embodiment generally outperforms the comparative example in terms of 0.33C charging capacity, 2C charging capacity retention, 1000-cycle capacity retention, and coating and scraping performance. Therefore, this application does not improve a single performance attribute solely by increasing specific surface area, sphericity, or graphitization degree, but rather achieves a comprehensive balance between processing performance, lithium-ion transport capacity, and cycle stability through matching specific surface area and sphericity, adjusting the ratio of ordered to disordered crystal structures, controlling thermally stable structures, and optimizing particle size distribution.
[0104] Alternatively or concurrently, the positive electrode active material may also be a commonly used positive electrode active material in the art, such as lithium cobalt oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, or nickel-cobalt-aluminum ternary materials. The conductive agent in the negative electrode may also be one or more of conductive carbon materials such as acetylene black, Ketjen black, carbon nanotubes, and graphene. The binder may also be one or more of aqueous binders such as polyacrylic acid, sodium polyacrylate, and sodium alginate. The solvent in the electrolyte may also be one or more of organic carbonate solvents such as propylene carbonate and diethyl carbonate. The separator may also be other types of separators such as polyethylene membranes and ceramic-coated separators.
[0105] In some other embodiments, the assembly method of the secondary battery can also adopt the stacking process instead of the winding process, and the cell shape can also be a square hard-shell cell or a cylindrical cell. The above changes do not affect the application effect of the negative electrode active material of this disclosure in the secondary battery.
[0106] It should be understood that the features described in the above embodiments can be combined with each other in any manner without conflict. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the spirit and scope of this disclosure. All such modifications and variations should fall within the protection scope defined by the appended claims.
Claims
1. A negative electrode active material, characterized in that, include: A graphite core, and an amorphous carbon layer disposed on at least a portion of the surface of the graphite core; The specific surface area Rm of the negative electrode active material 2 / g is 1m 2 / g~6m 2 / g; The sphericity ψ of the negative electrode active material is 0.7~0.96; The X-ray diffraction pattern of the negative electrode active material has a first diffraction peak in the range of 26.5°~26.8° with a diffraction angle 2θ, and the peak intensity of the first diffraction peak is V1; it has a second diffraction peak in the range of 41.7°~42.5° with a diffraction angle 2θ, and the peak intensity of the second diffraction peak is V2, and the half width at half maximum (W2°) of the second diffraction peak is W2°, and satisfies: 0.136≤V2 / [(W2-0.7)×V1]≤1.
05.
2. The negative electrode active material according to claim 1, characterized in that, The negative electrode active material satisfies: 0.6≤(ψ-0.6)×R≤0.
9.
3. The negative electrode active material according to claim 1, characterized in that, The negative electrode active material satisfies the following condition: 2% ≤ (m1-m2) ≤ 14%. In the formula, m1 represents the normalized residual mass fraction of the thermogravimetric curve of the negative electrode active material at 410℃, and m2 represents the normalized residual mass fraction of the thermogravimetric curve of the negative electrode active material at 495℃.
4. The negative electrode active material according to claim 3, characterized in that, The m1 is 97.2%~99.6%, and the m2 is 89.9%~96.5%.
5. The negative electrode active material according to claim 3, characterized in that, The compaction density of the negative electrode active material at 5T is P g / cm³. 3 1.55 g / cm 3 ~1.67 g / cm 3 .
6. The negative electrode active material according to claim 1, characterized in that, The cumulative particle size Dv of the negative electrode active material 50 The size ranges from 6μm to 12μm.
7. The negative electrode active material according to claim 6, characterized in that, The cumulative particle size Dv of the negative electrode active material 99 The range is 30μm to 42μm.
8. The negative electrode active material according to claim 7, characterized in that, The negative electrode active material Dv 50 and Dv 99 Satisfies: 1.7 ≤ (Dv) 99 -Dv 50 ) / Dv 50 ≤2.
8.
9. The negative electrode active material according to claim 7, characterized in that, The degree of graphitization of the negative electrode active material is 91%~96%.
10. A secondary battery, characterized in that, The invention includes a negative electrode sheet, the negative electrode sheet comprising a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector, the negative active material layer comprising a negative active material according to any one of claims 1 to 9, wherein the number of continuous scratches greater than or equal to 3 mm on the surface of the negative active material layer is less than or equal to 1.
11. The secondary battery according to claim 10, characterized in that, The curvature κ of the formation differential capacity curve of the secondary battery at 2480mV satisfies: 0.09≤κ≤0.
15.
12. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 10 or 11, wherein the secondary battery serves as the power supply for the electrical device.